ALQURAN DAN AFLIKASINYA DALAM PENDIDIKAN - Siregar, Dame (FORUM PAEDAGOGIK, 2014)
AbstractThe application of good Muslim personality especially in IAIN Padangsidimpuan on Al-Qur’an and hadist must be from a formal Islamic custom and culture firstly. Further, there must be a role or policy for illegal man and woman couple inside and outside of campus. The certification for teachers and lectures must create a lesson plan on a good Muslim personality approach (character) to sharper students and stronger them in study, not let them chat or talk something not with relevance to what must be expected as their responsibility.Keywords: Al-Qur’an and guidence of a life